1998
DOI: 10.1016/s0735-1097(98)00496-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of exercise capacity by sarpogrelate as a result of augmented collateral circulation in patients with effort angina

Abstract: Sarpogrelate augments flow reserve of the collateral circulation and improves exercise capacity in anginal patients with well-developed collaterals. These findings indicate that a serotonin blocker, sarpogrelate, is useful not only as an antiplatelet drugs, but as an antianginal drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…4 Our results also showed novel actions of sarpogrelate on IR and adiponectin modification, which are supported by the results of a recent experimental investigation in OLETF rats 26 and clinical data from diabetic patients. 14 The mechanisms of these beneficial actions on IR remain unclear.…”
Section: Ir Modification By Serotonin 2a Receptor Antagonistsupporting
confidence: 88%
See 2 more Smart Citations
“…4 Our results also showed novel actions of sarpogrelate on IR and adiponectin modification, which are supported by the results of a recent experimental investigation in OLETF rats 26 and clinical data from diabetic patients. 14 The mechanisms of these beneficial actions on IR remain unclear.…”
Section: Ir Modification By Serotonin 2a Receptor Antagonistsupporting
confidence: 88%
“…Various favorable cardiovascular pleiotropic actions of sarpogrelate have been reported. [1][2][3][4][5] A recent preliminary study by Yamakawa et al 14 showed a chronic increase in circulatory adiponectin and reduced HOMA-R in a small number of patients with treated diabetes mellitus (n=8) following sarpogrelate administration. Considering the wide range of actions of adiponectin on ASCDs, [13][14][15][16][17][18] sarpogrelate might have a beneficial effect on risk factor control and secondary prevention of ASCDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collateral vessels are more sensitive to vasoconstriction in response to serotonin than are normal vessels because of greater 5-HT 2A receptor-mediated sensitivity. A previous clinical trial demonstrated that sarpogrelate augments flow reserve of the collateral circulation and improves exercise capacity in anginal patients, 25) and this could be the mechanism for better physical function in PAD.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 22 patients with stable effort angina, oral administration of 200 mg of sarpogrelate 1 hour prior to treadmill exercise test was shown to improve exercise capacity and the severity score determined by myocardial perfusion scintigraphy in 12 patients with welldeveloped collateral flow evaluated by coronary angiography, whereas sarpogrelate affected neither exercise time nor severity score in other patients without collateral flow (Tanaka et al, 1998). This was confirmed in another study involving 2 weeks of treatment with 300 mg of sarpogrelate in 20 patients with stable angina pectoris (Kinugawa et al, 2002); treatment with sarpogrelate significantly increased the specific activity scale score, increased exercise time and rate-pressure product, an index of myocardial oxygen consumption, at onset of ischemic ST depression  0.1 mV on electrocardiogram, and decreased the number of anginal attacks only in patients with angiographically proven welldeveloped collateral flow.…”
Section: -Ht 2a Receptor Blocker and Treatment Of Cadmentioning
confidence: 97%